ŠESTI TOM BRILLOVOG GODIŠNJAKA - Kovač, Mirnes (Novi Muallim, 2022)
Prikaz knjige: Yearbook of Muslims in Europe, ur. Jørgen S. Nielsen, Samim Akgönül, Ahmet Alibašić i Egdūnas Račius, Brill, Leiden, 2014.)